Collaboration of Indigenous Communities and Academics in Creating Digital-Based Technology - Susilawati, Made; Syunikitta, Mirwanti; Silamat, Eddy; Mas’ud, Fadil; Nggandung, Yeheskial (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstrak Program Pengabdian Kepada Masyarakat melalui edukasi dan monitoring kepada masyarakat adat Bena bertujuan untuk memberdayakan masyarakat dengan keterampilan dan pengetahuan terkait teknologi digital. Tim pengabdi dalam hal ini akademisi berkolaborasi dengan masyarakat adat bersama-sama memanfaatkan kemajuan teknologi dengan tetap melestarikan adat yang ada. Kegiatan ini diawali dengan survei dan koordinasi dengan Perangkat Kampung Megalith Bena terkait permasalahan yang dihadapi masyarakat adat, Kemudian menyusun tim pengabdian masyarakat dan mengurus perijinan dengan perangkat desa. Selanjutnya pelaksanaan edukasi dan monitoring masyarakat adat Bena. Hasil kegiatan pengabdian yaitu literasi digital masyarakat adat Bena mengalami peningkatan secara signifikan serta berkontribusi pada pengembangan konten lokal terutama terkait kebudayaan di Kampung Bena seperti kegiatan menenun khas kampung Bena. Edukasi dan monitoring yang diberikan mewujudkan Desa adat yang adaptif terhadap era teknologi. Kata Kunci: Kolaborasi, masyarakat adat, akademisi, teknologi digital Abstract Community Service Activities through socialization and direct practice to the community by establishing a waste bank and managing waste based on the 3R principle aims to educate the community about the urgency of waste management in creating a clean and healthy environment. This activity was carried out in one of the villages in East Java, precisely in Trewung Village, Grati District, Pasuruan Regency, East Java. This activity began with a survey and coordination with the Trewung Village apparatus regarding the waste problems faced by the community. Then form a community service team and ask for permission from the Trewung Village Government, as well as implementing socialization by educating the community through socialization activities and implementing the establishment of a waste bank and waste management based on the 3R principle. The results of this community service activity are that the Trewung Village community is more educated and increasingly understands the importance of overcoming waste problems through the utilization of waste that can have economic value and proper waste management based on the 3R principle. This activity helps the community by socializing the importance of instilling a culture that creates a clean and healthy environment. Keywords: Waste bank, 3R, Independent village